Creating healthy places with the Place Standard Tool – An introduction. (30th September 2020) - Hasler, K; Howie, J
Abstract: This presentation will give an overview of the evidence around 'place' - the social AND physical environment - and how it impacts on lifelong health and wellbeing and health inequalities. It will provide a comprehensive introduction to the innovative Place Standard tool (PST) developed in partnership in Scotland - and how it translates complex health and place-making relationships into a simple set of questions. The resulting tool allows participants to identify strengths and weaknesses and begin to develop a shared understanding of place from which to take collaborative action to improve places and the lives of the people that use them. It will give a practical guide to how, when and where the PST can be deployed to support the delivery of healthy and equitable places, illustrated by real-life examples of use in a range of scales and contexts by the public sector and by communities across Scotland (and beyond) since its launch in 2015. It will also draw out the lessons learned during the first phase deployment and showcase the resultant versions that have been developed by the Scottish team to address identified gaps in a changing climate. These new versions, which will be launched in 2020, are: improvements to the main PST intended amongst other things to better enable place-based conversations to address health impacts of climate change; versions for children to support children's rights and participation; and a Design version aimed at architects and planners to support the design process to deliver healthier places. Key messages: The Place Standard tool is adaptable, easy-to-use and distils complex health evidence into simple questions relevant to a range of scales and types of real-life 'place'. As a practical, accessible framework for place-based conversations to support communities and agencies to together identify priorities for action to deliver high quality, sustainable places, it has proved highly transferable to a variety of contexts and countries.